Teratogens : chemicals which cause birth defects - Meyers, Vera Kolb (Studies in environmental science, 1988)
This multi-author work deals with the practical aspects of teratogens - chemicals which cause birth defects. It is designed for use as a unique guide to these chemicals in which one can find all relevant information. The issues covered include: how to obtain information about the teratogenic potential of chemicals; teratogenic chemicals in undergraduate chemistry laboratories; safe handling of teratogenic chemicals; teratogenicity of pesticides and other pollutants in the environment; occupational exposure and pregnancy outcome; identification and prevention of reproductive hazards in industry; and the long-term effects of chemicals on the developing brain. A list of approximately 5,000 chemicals known to cause reproductive effects is given. A comprehensive bibliography is included with each chapter providing up-to-date references for more in-depth coverage. The monograph will be of interest to academic and industrial chemists, health professionals, as well as both undergraduate and graduate students in health and related sciences.